In Vivo versus Augmented Reality Exposure in the Treatment of Small Animal Phobia: A Randomized Controlled Trial - Botella, Cristina; Pérez-Ara, M. Ángeles; Bretón-López, Juana; Quero, Soledad; García-Palacios, Azucena; Baños, Rosa María (PLOS ONE, 2016)
Although in vivo exposure is the treatment of choice for specific phobias, some acceptability problems have been associated with it. Virtual Reality exposure has been shown to be as effective as in vivo exposure, and it is widely accepted for the treatment of specific phobias, but only preliminary data are available in the literature about the efficacy of Augmented Reality. The purpose of the present study was to examine the efficacy and acceptance of two treatment conditions for specific phobias in which the exposure component was applied in different ways: In vivo exposure (N = 31) versus an Augmented Reality system (N = 32) in a randomized controlled trial. “One-session treatment” guidelines were followed. Participants in the Augmented Reality condition significantly improved on all the outcome measures at post-treatment and follow-ups. When the two treatment conditions were compared, some differences were found at post-treatment, favoring the participants who received in vivo exposure. However, these differences disappeared at the 3- and 6-month follow-ups. Regarding participants’ expectations and satisfaction with the treatment, very positive ratings were reported in both conditions. In addition, participants from in vivo exposure condition considered the treatment more useful for their problem whereas participants from Augmented Reality exposure considered the treatment less aversive. Results obtained in this study indicate that Augmented Reality exposure is an effective treatment for specific phobias and well accepted by the participants.